Estudio de factibilidad para la implementación de un software para la administración de los materiales ingresados en una bodega de la empresa Electconstru S.A. de la ciudad de Babahoyo - Quinto Sandoya, Wilson Gabriel (2020)
This project was carried out to meet the need to improve the storage process with the implementation of a software for the management of materials, in the company ELECTCONSTRU S.A. For which the study was carried out and the necessary information was collected to improve information processing, which is currently done manually, generating problems and little reliability when wanting to liquidate a project. To carry out this project, a descriptive field study was implemented, surveys were implemented to find out how the company was handling the materials, quantitative and qualitative methods were used. Once all the important requirements had been obtained, the conceptual method in which the objects are represented and show a simplified vision of the system was developed, models were used to meet the objective of managing materials from the company's warehouse, providing safe and reliable information to aid in future decision making.